Cereblon enhancer methylation and IMiD resistance in multiple myeloma - Haertle, Larissa; Barrio, Santiago; Munawar, Umair; Han, Seungbin; Zhou, Xiang; Vogt, Cornelia; Fernandez, Rafael Alonso; Bittrich, Max; Ruiz-Heredia, Yanira; Da Via, Matteo; Zovko, Josip; Garitano-Trojaola, Andoni; et al. (Blood, 2021)
Cereblon is the direct binding target of the immunomodulatory drugs (IMiDs) that are commonly used to treat multiple myeloma (MM), the second most frequent hematologic malignancy. Patients respond well to initial treatment with IMiDs, but virtually all patients develop drug resistance over time, and the underlying mechanisms are poorly understood. We identified an as yet undescribed DNA hypermethylation in an active intronic CRBN enhancer. Differential hypermethylation in this region was found to be increased in healthy plasma cells, but was more pronounced in IMiD-refractory MM. Methylation significantly correlated with decreased CRBN expression levels. DNA methyltransferase inhibitor (DNTMi) in vitro experiments induced CRBN enhancer demethylation, and sensitizing effects on lenalidomide treatment were observed in 2 MM cell lines. Thus, we provide first evidence that aberrant CRBN DNA methylation is a novel mechanism of IMiD resistance in MM and may predict IMiD response prior to treatment.
CRIS-Team Scopus Importer:2023-03-23